Inclusión de harina de algarrobo (Prosopis chilensis) en la dieta de pollos cobb 500 sobre los parámetros de salud y productivos - Moreira Zambrano, Sonia María (2019)
The objective of this thesis was to evaluate the inclusion of carob flour (Prosopis chilensis) in the diet of Cobb 500 chickens on health and production parameters. 360 birds were used which were designated to a Completely Random Design, with 3 treatments (T0: Control treatment; T1 Inclusion of 15% Algarrobo Flour and T2 Inclusion of 25% Algarrobo Flour) and 10 repetitions. The data was analyzed using an analysis of variance, using a 5% Tukey test with the statistical package InfoStat (2018). In the evaluation of the productive variables, significant differences were found (P = 0.005), in which the animals of T1 achieving a greater weekly weight (2893.97 g ± 28.47) and accumulated weekly weight gain (2844.91 g ± 28.49); but T0 achieved the highest efficiency in food conversion (1.63). In addition, greater results were found in the yield to the channel (80.06%); viability (99.17%) and European efficiency index (444.97) in the T0. No significant differences were found between treatments (P = 0.0005) on the health variable in measurements and weights of immunological organs. It is concluded that the feeding of Cobb 500 fat chickens with carob flour did not disadvantage the productive variables of the diets supplied and can be used to improve the productive yield in Cobb 500 chickens without affecting their health.